Preliminary Investigation of The Potential of Coconut Sugar Production Using Dwarf Varieties - Novarianto, Hengky; Tulalo, Meity A.; Mawardi, Sukmawati (International Coconut Community Journal, 2021)
Coconut sugar is one of the high economic value products. The production of coconut sugar In Indonesia is about 300,000 tonnes/year. During the last few years, the supply of raw materials for the coconut sugar product has diminished due to stagnant production caused by the lack of coconut climbers collecting coconut sap. The scarcity of labor is caused by several factors, especially young tappers who are less interested in climbing tall coconut palms. To solve this problem, it is necessary to evaluate the potency of dwarf coconuts, with short trunk and fast fruiting. The objective of this study was the evaluation and selection of Dwarf coconut varieties that have high yield potential as a producer of sap and coconut sugar. The research was conducted in North Sulawesi Province by evaluating 9 Dwarf coconut varieties. The results of research on the production of coconut sap and sugar from 9 Dwarf coconut varieties with different plant ages, gave mixed results among coconut varieties. The length of tapping sap varied between 31.42 - 43.21 days/bunch, the volume of sap varied between 1.1 - 3.3 liters/tree/day, the pH of sap ranged between 6.49 - 7.86 and the Brix value varied between 14.01 - 17.64. The most important traits such as the sap yield and sugar production also varied from 14.54 to 18.95% among varieties, and between 0.16 to 0.42 kg/tree/day respectively. The Dwarf coconut varieties with the highest potential yield of sap and sugar are the Waingapu Red Dwarf (WRD), Salak Green Dwarf (SGD), and Nias Yellow Dwarf (NYD), with the potential sugar yield of 2.09 tons, 1.64 tons, and 1.56 tons/month/ha respectively. It is hoped that these Dwarf coconut varieties would be attractive for young tapers and could be introduced to farmers in several Provinces for tapping purposes for the production of coconut sugar.